2021
DOI: 10.3389/fmicb.2020.604544
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ESBL/AmpC-Producing and Fosfomycin-Resistant Escherichia coli From Different Sources in Poultry Production in Southern Brazil

Abstract: This study discussed the use of antimicrobials in the commercial chicken production system and the possible factors influencing the presence of Extended-spectrum β-lactamase (ESBL)/AmpC producers strains in the broiler production chain. The aim of this study was to perform longitudinal monitoring of ESBL-producing and fosfomycin-resistant Escherichia coli from poultry farms in southern Brazil (Paraná and Rio Grande do Sul states) and determine the possible critical points that may be reservoirs for these strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 66 publications
(84 reference statements)
4
18
0
Order By: Relevance
“…Co‐selection is particularly relevant for resistances encoded by genes, e.g. ESBL or mcr ‐, located on the same MDR plasmid as genes for more commonly used antimicrobials (Gazal et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…Co‐selection is particularly relevant for resistances encoded by genes, e.g. ESBL or mcr ‐, located on the same MDR plasmid as genes for more commonly used antimicrobials (Gazal et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…The One Health concept allows for a greater understanding of the scope of this issue ( Thanner et al, 2016 ; Aslam et al, 2021 ; Gazal et al, 2021 ), given the connection that exists between human, animal, and environmental health ( Aslam et al, 2018 ; Aarestrup et al, 2021 ). Through this, the World Health Organization (WHO), together with the United Nations Food and Agriculture Organization and the World Organization for Animal Health, have promoted the monitoring and surveillance of resistance to antimicrobials, aiming to detect the possible causes and main points responsible for the selection of multiresistant strains ( Poirel et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already shown that the poultry environment ( Cunha et al, 2017 ; Saharan et al, 2020 ; Gazal et al, 2021 ) and its products ( Koga et al, 2015 ; Davis et al, 2018 ; Cyoia et al, 2019 ) are responsible for harboring and transmitting multidrug-resistant (MDR) strains that produce extended-spectrum β-lactamase (ESBL) or other mechanisms with resistance to antimicrobials, that are considered the last resort in human medicine, such as fosfomycin and colistin ( WHO, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The high bacterial exposure to β -lactam antibiotics in poultry farming, usually through feed additives and clinical or prophylactic treatments, leads to the exclusion of sensitive strains but spares the resistant mutant ones. ESBL and AmpC enzymes have the ability to hydrolyze a number of β -lactam antimicrobials such as cephalosporins and monobactams [ 2 ]. In the long run, this increases the difficulty of treating infections, especially in the human sector where β -lactams are more used.…”
Section: Introductionmentioning
confidence: 99%
“…ough poultry is taken as one of the major reservoirs of antimicrobial-resistant bacteria [5], limited findings on some categories of antimicrobial-resistant bacteria (ARB) such as extended-spectrum β-lactamase-and AmpCproducing E. coli still exist. e geographical distribution of ESBL and AmpC E. coli in poultry differs with some studies portraying worrying prevalence rates of over 20% in chickens [2,[11][12][13][14]. eir information is not clear on the interplay between the microbes, their earmarked hosts, and the aspects stimulating carriage and dissemination.…”
Section: Introductionmentioning
confidence: 99%